Утворення ультрадисперсних залізооксидних фаз на поверхні сталі в умовах контакту з водними розчинами двовалентної міді і благородних металів - Лавриненко, О.М. (Мінералогічний журнал, 2010)
Досліджено особливості формування ультрадисперсних залізооксидних фаз на поверхні сталі, що контактує з водними розчинами міді, срібла, золота, платини та паладію в умовах вільного надходження до системи окисника. Показано, що за значень вихідної концентрації Cu(II), Ag(I), Au(III), Pt(VI) від 1 до 10 мг/дм³ на поверхні сталі утворюється фаза феришпінелі (магнетиту). Механізм взаємодії катіонів електропозитивних металів з залізооксидними фазами у системі сталевого електрода пов’язаний з формуванням поверхневих структур Green Rust, адсорбцією та відновленням катіонів дисперсійного середовища на їх поверхні й у міжшаровому просторі з окисненням Fe(II) у кристалічних ґратках з фазовим перетворенням на магнетит або оксигідроксиди заліза. Отримані ультрадисперсні композити, що складаються з магнетиту (в присутності Cu(II), Ag(I), Au(III), Pt(VI)) або лепідокрокіту (в присутності Pd(II)) і відновленого електропозитивного металу, внаслідок перенесення у водне дисперсійне середовище набувають колоїдної стійкості і не трансформуються під час контакту з окисником, що робить їх перспективним матеріалом для застосування у медико-біологічних системах. Исследованы особенности формирования ультрадисперсных железооксидных фаз на поверхности стали, контактирующей с водными растворами меди, серебра, золота, платины и палладия в условиях свободного доступа в систему окислителя. Показано, что при исходных значениях концентрации Cu(II), Ag(I), Au(III), Pt(VI) от 1 до 10 мг/дм³ на поверхности стали образуется фаза ферришпинели (магнетита). Механизм взаимодействия катионов электроположительных металлов с железооксидными фазами в системе стального электрода связан с формированием поверхностных структур Green Rust, адсорбцией и восстановлением ка тионов дисперсионной среды на их поверхности и в межслоевом пространстве с окислением Fe(II) в кристал лической решетке и фазовым превращением в магнетит или оксигидроксиды железа. Ультрадисперсные ком позиты, состоящие из магнетита (в присутствии Cu(II), Ag(I), Au(III), Pt(VI)) или лепидокрокита (в присутствии Pd(II)) и восстановленного на их поверхности электроположительного металла, в результате переноса в водную дисперсионную среду приобретают коллоидную устойчивость и не трансформируются во время контакта с окислителем, что создает перспективу для их использования в медико-биологических системах. The interest in new iron oxide structures with different physico-chemical properties was connected with a necessity of creating the functional materials for medical and biological aims. On the one hand the most claimed nanosized ferromagnetic materials are the natural analogs of ultradisperse iron oxides such as magnetic Fe₃O₄, maghemite γ-Fe₂O₃ or spinel ferrite of 3d-metals, that was shown in our previous article, but on the other hand these are varied composite materials containing the ferromagnetic nucleus and coats of noble metals. This article shows the specifics of formation of iron oxide structures and their composites on the iron surface contacting with water solution that included electropositive metal with respect to iron cations, such as copper, silver, gold, platinum, and palladium. The main method of investigation was XRD with an additional module, which permits to register phase composition of surface structures in situ and transmission electron microscopy (TEM). The formation of the structure took place on the surface of the steel electrode (St3) or its near-surface layer by its contact with air oxygen and dispersion medium. As dispersion medium there was used the water solution of CuSO₄, AgNO₃, PtCl₄, PdCl₂ and HAuCl₄ at pH ranging from 2.5 to 12.0 for copper and silver and their concentrations from 1 to 100 mg/dm³. At the initial stage of the process of the formation of iron oxide structures on the iron surface in the silver-containing medium the ultra disperse structures of Fe(II)-Fe(III) LDH and iron oxyhydroxides–goethite α-FeOOH and lepidocrokite γ-FeOOH were formed there. The process of phase formation goes by stages including the growth of nanosized particles of Green Rust I, its transformation to phases of iron oxyhydroxides and their interaction with silver from the dispersion medium with formation of the composite of magnetite Fe₃O₄ and metal silver. The addition of other precious metals into dispersion medium by processing phase formation has shown the same result. The ultradisperse phase of magnetite Fe₃O₄ with inclusions of ions of Cu(II), Pt(IV), Pd(II) and Au(III) was formed on the surface of the steel electrode. The identity of phase composition of iron oxide minerals in wide range of pH value allows us to think that the specific conditions are created on the iron surface that resulted in electrochemical reactions of iron dissolution and oxygen depolarization. The mechanism of phase formation in the presence of electropositive metals depends on physico-chemical conditions of the experiment performance. The optimal condition of phase formation was found, and the TEM images of these composites were represented in the article. The composites of magnetite Fe₃O₄ with inclusions of precious metals are promising for medical-biological investigation such as magnetic separation of biological objects or vector drug delivery in the magnetic field.